2014
DOI: 10.1378/chest.14-0566
|View full text |Cite
|
Sign up to set email alerts
|

Nurse Practitioner/Physician Assistant Staffing and Critical Care Mortality

Abstract: NPs/PAs appear to be a safe adjunct to the ICU team. The findings support NP/PA management of critically ill patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
31
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(35 citation statements)
references
References 37 publications
2
31
0
2
Order By: Relevance
“…As in our study, there was no difference in clinical competencies (ie, history taking, physical exam, communication, and report) between PAs and residents in anaesthesiology and surgery . Furthermore, studies in the ICU reported the same quality of care by teams with PAs in comparison with teams without PAs . In these studies, quality of care was measured by clinical indicators, for instance, mortality, fewer, pain or infections.…”
Section: Discussionsupporting
confidence: 57%
“…As in our study, there was no difference in clinical competencies (ie, history taking, physical exam, communication, and report) between PAs and residents in anaesthesiology and surgery . Furthermore, studies in the ICU reported the same quality of care by teams with PAs in comparison with teams without PAs . In these studies, quality of care was measured by clinical indicators, for instance, mortality, fewer, pain or infections.…”
Section: Discussionsupporting
confidence: 57%
“…In some cases, advanced practice providers have been added to traditional physician staffing models, and in other cases, they have assumed duties traditionally performed by physicians (6)(7)(8)(9)(10)(11). Although NPs were first introduced to the healthcare workforce in the 1960s (12,13), the use of NPs as providers in the ICU is a relatively recent development that has expanded rapidly (14).…”
mentioning
confidence: 99%
“…Yet despite the proliferation of NPs in the critical care workforce, studies examining outcomes in ICUs staffed by advanced practice providers with traditional models are limited. Recently, Costa et al (14) published a multicenter study comparing outcomes in ICUs in which advanced practice providers were part of the ICU team versus ICUs without advanced practice provider participation. Published data on outcomes in ICUs in which NPs completely replaced a part of the physician team (i.e., resident physicians) are limited to one study (7).…”
mentioning
confidence: 99%
“…Instead, efforts could be directed at expanding other organizational factors, such the number of bachelors prepared nurses and improved nursing work environments, which are associated with lower mortality (19). Efforts might also be directed at expanding care models in which intensivists don’t directly manage every patients but instead simply oversee the ICU, with direct day-to-day care provided by hospitalists or nurse practitioners/physician assistants (20, 21). These models may be more feasible than bringing high-intensity daytime staffing to ICU, and, as evidenced by this study, may bring similar results.…”
Section: Discussionmentioning
confidence: 99%